Development of Stunting Prevention Education Videos through Balanced Nutrition Arrangements for Adolescents - Suiraoka, I Putu; Nursanyoto, Hertog; Fritalia, Ita (Poltekkes Kemenkes Palu, 2024)
Stunting in children contributes to adolescent nutrition problems because adolescent nutrition affects the health quality of the next generation. Adolescent malnutrition, such as iron and protein deficiencies, impacts reproductive health and increases the risk of giving birth to stunted children. Therefore, it is important to carry out adolescent nutritional interventions to prevent stunting as early as possible. This research aims to produce educational videos that are feasible and effective in increasing knowledge about stunting and balanced nutrition with the target group of adolescents. This research is a Development Research using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. The data analysis applied a one-to-one test and a small-group test. The one-to-one test obtained a percentage of 89% indicating that the video design is in a good category with revision. The small-group test reached 92% indicating that it is categorized as very good but some suggestions for improvement are recommended. The suggested revision is not fundamental because it is only related to the selection of vocabulary to be understood better by the target. Another recommendation is the background musical illustrations that possibly distract the targets’ attention. After some improvements, it is recommended that this educational video be disseminated through social media platforms such as WhatsApp Group or Instagram so that more teenagers can access it.